Development of Novel Conjugated Polyelectrolytes as Water-Processable Interlayer Materials for High-Performance Organic Photodiodes - Yoon, Seongwon; Jo, Jea Woong; Yu, Seong Hoon; Yung, Jae Hoon; Son, Hae Jung; Chung, Dae Sung (AMER CHEMICAL SOC, 2017)
A series of novel conjugated polyelectrolytes composed of two different building blocks with different composition ratios were designed and synthesized for application as a functional layer in high-performance organic photodiodes (OPDs). A homopolymer and two random copolymers were prepared using different molar ratios of dibromo 1,4-bis(4-sulfonatobutoxy)benzene (SPh) and dibromo 1,4-bis(4-tetraethylene glycol)benzene (EGPh): EG20 with SPh:EGPh ratio of 0.8:0.2 and EG40 with a ratio of 0.6:0.4. Structural analyses by two-dimensional grazing-incidence X-ray diffraction and near-edge X-ray absorption fine structure spectroscopy studies proved that a higher EGPh content could induce more organized polymer chains with face-on orientation of EG20 and EG40. Such an orientation of EG20 and EG40 along with the ordered crystalline organization yielded effective molecular dipole moments in the thin films when applied as an interlayer between ZnO and an active layer of inverted OPDs. As confirmed by ultraviolet photoelectron spectroscopy, the increase in EG content gradually shifted the workfunction of the ZnO, facilitating the inverted OPD to simultaneously achieve a decrease in dark current and enhancement in photocurrent. The synergetic effects introduced by the newly designed EG20 and EG40 resulted in significantly improved OPD performances with high specific detectivity up to 2.1 x 10(13) Jones, 3 dB bandwidth of 72 kHz, and linear dynamic range of 110 dB.
Keywords: POLYMER SOLAR-CELLS; INTERFACIAL LAYER; HIGH-EFFICIENCY; SIDE-CHAIN; BILAYER CATHODE; PHOTODETECTORS; ORIENTATION; COPOLYMERS